DETERMINANTS OF ECO-CONSCIOUS CONSUMER BEHAVIOR OF MUSLIMS IN INDONESIA USING THE THEORY OF PLANNED BEHAVIOR - Nasr, Sumayyah Amalina; Safira, Anya (UI Scholars Hub, 2021)
Manuscript type: Research paper Research Aims: This study aims to analyze the determinants of eco-conscious behavior of Indonesian Muslim consumers by using the Theory of Planned Behavior, with the incorporation of several additional variables namely intrinsic religious orientation, green trust, and environmental concern. Design/methodology/approach: The analysis used for this research is Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPLS software. Research Findings: The results show that intrinsic religious orientation influences the eco-conscious behavior of Indonesian Muslims directly and indirectly through attitude toward green products. Furthermore, environmental concern influences the eco-conscious behavior of Indonesian Muslims directly and indirectly through subjective norm and perceived behavioral control as mediators. Meanwhile, green trust does not directly influence the eco-conscious behavior of Indonesian Muslims. Theoretical Contribution/Originality: as a literature related to the theory of planned behavior that correlates religious and marketing factors to a person’s eco-conscious behavior. Practitioner/Policy Implication: Analyzing the factors that influence attitudes and behavior related to environmental awareness will make consumers more understand existing environmental problems. Furthermore, the results of this study may be useful for green marketers in shaping marketing policies and strategies. Research limitation/Implications: There are supporting variables to analyze attitudes and behaviors that explain pro-environment in previous studies but have not been included in this study. Then, more elaborated moderating effects shaped by intrinsic religious orientation is needed.